Concise synthesis of (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate - Ramalingam, S.; Bhise, Ankushkumar D.; Show, Krishanu; Kumar, Pradeep (Arkivoc, 2013)
An efficient synthesis of (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate 1, a common intermediate for various polyhydroxylated piperidines is reported in six steps with 32% overall yield starting from Garner's aldehyde. The key steps include the diastereoselective nucleophilic addition and intramolecular cyclization. (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate is a common precursor for the synthesis of 1-deoxy-L-mannojirimycin, 1-deoxy-L-idonojirimycin, L-fagomycin and related analogues.
Keywords: cyclization; Garner's aldehyde; nucleophilic addition; polyhydroxy piperidines

Chemoselective deprotection of N-allylic amines using DDQ - Kumar, Pradeep; Cherian, Shijo K.; Jain, Ruchi; Show, Krishanu (Tetrahedron Letters, 2014)
A highly chemoselective and simple method for the deprotection of N-allylic amines using DDQ has been developed. The use of DDQ in dichloromethane-water provides a mild and efficient one-step deallylation of a wide variety of orthogonally protected tertiary amine derivatives. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Chemoselective deprotection; DDQ; N-Allylic amines; Orthogonally protected tertiary amines